2021
DOI: 10.1021/acs.analchem.1c02259
|View full text |Cite
|
Sign up to set email alerts
|

Accurate and Nonpurified Identification of Extracellular Vesicles Using Dual-Binding Recognition Mode

Abstract: Circulating extracellular vesicles (EVs) are promising biomarkers for the early diagnosis and prognosis of cancer in a non-invasive manner. However, the rapid and accurate identification of EVs in complex biological samples is technically challenging, which is attributed to the requirement of extensive sample purification and unsatisfactory detection accuracy due to the disturbance of interfering proteins. Herein, a simultaneous binding of double-positive EV membrane protein-based recognition mode (DRM) is pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…However, the lowest expression of EpCAM was observed for EXO-PANC-1 compared to that for the two other exosomes (Figure A), which agrees with reported studies . AICHA was also assessed by detecting CD63 for exosomes derived from the three cancer cell lines; the obtained results in Figure B found that the expression of CD63 in EXO-PANC-1 and EXO-LOVO were higher than that of EXO-MCF-7, which are in accordance with previous literature. ,, The obtained results indicate that AICHA enables adaptation for profiling, offering a promising platform for exosome proteomic studies, cancer diagnosis and classification, as well as monitoring cancer recurrence.…”
supporting
confidence: 91%
“…However, the lowest expression of EpCAM was observed for EXO-PANC-1 compared to that for the two other exosomes (Figure A), which agrees with reported studies . AICHA was also assessed by detecting CD63 for exosomes derived from the three cancer cell lines; the obtained results in Figure B found that the expression of CD63 in EXO-PANC-1 and EXO-LOVO were higher than that of EXO-MCF-7, which are in accordance with previous literature. ,, The obtained results indicate that AICHA enables adaptation for profiling, offering a promising platform for exosome proteomic studies, cancer diagnosis and classification, as well as monitoring cancer recurrence.…”
supporting
confidence: 91%
“…16 Consequently, aptamers are widely used in the field of biosensors for disease diagnosis, the detection of antibiotics, toxins and microorganisms, and so on. 17–20…”
Section: Introductionmentioning
confidence: 99%
“…16 Consequently, aptamers are widely used in the field of biosensors for disease diagnosis, the detection of antibiotics, toxins and microorganisms, and so on. [17][18][19][20] A G-quadruplex (G4), a special secondary structure of nucleic acids, is composed of four successive guanine (G) segments on a single strand nucleic acid. 21,22 Numerous studies have found that the G-quadruplex structure plays a significant role in gene stability, telomere synthesis, gene transcription and translation regulation, gene recombination and other life processes.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al reported a double-aptamer recognition system based on a hyperbranched DNA superstructure that promotes signal amplification and ratiometric dual-signal strategies . Sun et al developed an identification strategy of nonpurified exosomes by the combination of the double-positive exosome membrane protein recognition-mediated toehold activation and the G-quadruplex DNAzyme-catalyzed etching of Au@Ag nanorods . Li et al proposed an aptamer-based logic gate with numerous protein biomarkers on single exosomes as input and thermophoretic accumulation amplified signals as output, achieving 97% identification accuracy for breast cancer patients .…”
mentioning
confidence: 99%
“…29 Sun et al developed an identification strategy of nonpurified exosomes by the combination of the double-positive exosome membrane protein recognition-mediated toehold activation and the G-quadruplex DNAzyme-catalyzed etching of Au@Ag nanorods. 30 Li et al proposed an aptamer-based logic gate with numerous protein biomarkers on single exosomes as input and thermophoretic accumulation amplified signals as output, achieving 97% identification accuracy for breast cancer patients. 12 These double-aptamer detection strategies enhance the accuracy of exosome detection significantly, but they usually require a tedious signal amplification process to improve the sensitivity.…”
mentioning
confidence: 99%